Rancang Bangun Sistem Pendingin Pada Photovoltaic Dengan Monitoring Berbasis IOT - Ferdi Arisandi; Sunardi (CV. ULIL ALBAB CORP, 2024)
Solar energy, as a renewable energy source, holds significant potential in Indonesia due to its equatorial location, which ensures sunlight throughout the year. However, high temperatures and excessive solar radiation can reduce the efficiency of photovoltaic (PV) modules. The purpose of this study is to design an effective cooling system to improve the efficiency of PV and to develop an IoT-based monitoring system to monitor the system's performance in real-time. This cooling method utilizes a water spray nozzle and DS1820 sensors to monitor both the panel surface temperature and the water temperature. Test results show that PV systems with the cooling system produce an average output voltage of 15.15 V, a current of 2.61 A, and a power of 39.54 W, with a power efficiency of 17.17%. In contrast, PV systems without cooling only produce an average output voltage of 13.52 V, a current of 1.6 A, and a power of 21.63 W, with a power efficiency of 9.38%. The implementation of the cooling system improves power efficiency by 82.89%. The difference in power output between the PV with the cooling system and without the cooling system is 17.91 W.